EFISIENSI PROGRAM PEMULIHAN EKONOMI NASIONAL TERHADAP DAMPAK PANDEMI COVID-19 PADA KESEJAHTERAAN MASYARAKAT - Yassinta Ben Katarti Latiffa Dinar (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2022)
This study aims to assess the efficiency of the National Economic Recovery (PEN) program budget launched by the government to reduce the impact of the pandemic on public welfare in 34 provinces in Indonesia. Efficiency measurements computed using Data Envelopment Analysis (DEA) show that only 12 provinces are efficient at holding the increase in poverty and unemployment by implementing the PEN budget. West Papua Province is efficient despite its unemployment and poverty levels being higher than the national average. West Java Province is likely inefficient and can potentially reduce the unemployment rate with the PEN budget implementation if it is efficient. Maluku Province has the potential to further reduce its poverty with the PEN budget if it is efficient. Not all provinces with low unemployment and poverty rates efficiently implement the PEN budget and vice versa. This study evaluates the regional government's performance from an efficiency point of view. The efficient provinces discovered from the research can become a benchmark for other provinces to maximize the decline in welfare indicators by using the available budget.